Relationships between Levels of Patient Satisfaction and Various External Factors in the Healthcare Industry: Part 3 (International Journal of Innovative Research in Computer Science & Technology, 2018)
Increasingly knowledgeable consumers,  with rising demands to have information available for  them to make appropriate health care decisions, have  driven healthcare managers and administrators to  focus on an improvement of the service quality to  increase patient’s satisfaction. As efforts, many of  them are trying to adapt well-established, successful  business models like total quality management (TQM),  and quality function deployment (QFD) and also trying  to learn in what aspects of the health care service  provision generate or inhibit patient satisfaction. The  primary objective was to discuss issues when employing  the models to health care industries.
Keywords: Healthcare; Measurement; Satisfaction; Patient; Evaluation